BiFeO3 thin film with nested skyrmions and its preparation method and application
By using pulsed laser deposition method to prepare BiFeO3 films on specific substrates, the problem of slow progress in research on nested sigminos in BiFeO3 materials in the prior art was solved, and efficient and controllable nested sigminos preparation was achieved, and the Its application in ferroelectric memory and spintronic devices.
Patent Information
- Application Number
- CN202411479442.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art cannot effectively prepare BiFeO3 materials with nested sgmidones through simple methods, and there are huge challenges in controlling their boundary conditions, resulting in slow research progress.
Bi1.03FeO3 was deposited on a specific (LaAlO3) 0.29 (SrTa1/2Al1/2O3) 0.71 substrate by pulsed laser deposition method, and prepared by preset cooling rate and process parameters (temperature, oxygen pressure, laser energy, deposition rate, time). BiFeO3 film with nested sgmidones was produced.
The preparation of BiFeO3 films with nested sgmidons was realized, which simplified the process flow, improved the controllability of the preparation, and opened up its application prospects in ferroelectric memory and spintronic devices.
Smart Images

Figure CN119020726B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nested skyrmion materials, and in particular to a BiFeO3 film with nested skyrmions and a preparation method and application thereof. Background Art
[0002] In recent years, the polarization topological domain structure in nano-ferroelectric thin films has been one of the research hotspots in the field of condensed matter physics and high-density non-volatile memory due to its special polarization structure and excellent physical properties. Among them, BiFeO3 is a promising multiferroic material. As the only room temperature single-phase multiferroic material that has both ferroelectricity and (antiferromagnetism) and is environmentally friendly, regulating its potential topological domain structure has always been an important scientific and technological issue in the field.
[0003] Skyrmions are topological domain patterns intrinsically embedded in ferroelectric materials, which are conducive to high-density information storage. They have rich physical properties and broad device application prospects, and provide a new platform for studying new nanoscale topological structures and their polar properties.
[0004] However, due to the huge challenges in controlling complex boundary conditions, research on BiFeO3 materials with nested skyrmions is still progressing slowly, and it is still impossible to effectively prepare BiFeO3 materials with nested skyrmions through simple methods.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] Based on the above-mentioned deficiencies of the prior art, the purpose of the present invention is to provide a BiFeO3 film with nested skyrmions and a preparation method and application thereof, aiming to solve the problem that BiFeO3 materials with nested skyrmions cannot be effectively prepared by a simple method.
[0007] The technical solution of the present invention is as follows:
[0008] A first aspect of the present invention provides a method for preparing a BiFeO3 thin film having nested skyrmions, comprising the steps of:
[0009] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0010] Bi 1.03 FeO3 was used as the target material, and pulsed laser deposition was used to deposit (LaAlO3) oriented in the
[001] direction. 0.29 (SrTa1 / 2 Al 1 / 2 O3) 0.71 Deposition is performed on a substrate, and after cooling at a preset cooling rate, a BiFeO3 film with nested skyrmions is obtained;
[0011] The process parameters used in the pulsed laser deposition method are:
[0012] The temperature is 750~820℃, the oxygen pressure is 70~90mTorr, the laser energy is 300~370mJ, the deposition rate is 8~10Hz, and the deposition time is 5~32min.
[0013] Optionally, the thickness of the BiFeO3 film with nested skyrmions is 3-17 nm.
[0014] Optionally, the nested skyrmions are classified based on the angular change of the out-of-plane polarization direction of the nested skyrmions, and the type of the nested skyrmions is π-nested skyrmions, 2π-nested skyrmions or 3π-nested skyrmions.
[0015] Optionally, the BiFeO3 film with nested skyrmions contains a nano-island structure, the nano-island structure is composed of a plurality of nano-islands, and the ferroelectric polarization distribution of the BiFeO3 film containing a plurality of nano-islands presents a distribution configuration of polar nested skyrmions;
[0016] Taking the plane direction of the BiFeO3 film with nested skyrmions as the lateral direction and the thickness direction of the BiFeO3 film with nested skyrmions as the longitudinal direction, the average particle size of the multiple nano-islands in the lateral direction is 100~400nm, and the average particle size of the multiple nano-islands in the longitudinal direction is 2~3nm.
[0017] Optionally, when the deposition time is 6 to 9 minutes, the thickness of the obtained BiFeO3 film with nested skyrmions is 3 to 4.5 nm, the average particle size of the multiple nano-islands in the lateral direction is 100 to 200 nm, and the type of the nested skyrmions is π-nested skyrmions.
[0018] Optionally, when the deposition time is 10-15 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 6-7 nm, the average particle size of the multiple nano-islands in the lateral direction is 350 nm, and the type of the nested skyrmions is 2π nested skyrmions.
[0019] Optionally, when the deposition time is 25-32 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 14-17 nm, the average particle size of the multiple nano-islands in the lateral direction is 400 nm, and the type of the nested skyrmions is 3π nested skyrmions.
[0020] Optionally, the preset cooling rate is 5-10°C / min.
[0021] A second aspect of the present invention provides a BiFeO3 film with nested skyrmions, wherein the film is prepared by the preparation method of the present invention as described above.
[0022] The third aspect of the present invention provides an application of the BiFeO3 film with nested skyrmions as described above in a ferroelectric memory.
[0023] Beneficial effect: The present invention adopts pulsed laser deposition method to obtain (LaAlO3) with specific
[001] orientation. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The method provided by the present invention is simple and controllable, and can realize the industrial production of BiFeO3 thin films with nested skyrmions. The prepared BiFeO3 thin films with nested skyrmions have broad application prospects in ferroelectric memories and spintronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the cross section of a BiFeO3 film with nested skyrmions.
[0025] Figure 2 This is the X-ray diffraction pattern of the BiFeO3 film with nested skyrmions prepared in Example 1.
[0026] Figure 3 This is a graph showing the grazing incidence wide-angle X-ray scattering test results of the BiFeO3 film with nested skyrmions prepared in Example 1.
[0027] Figure 4 These are the piezoelectric force microscopy test results of the BiFeO3 film with nested skyrmions prepared in Example 1, where (a) is a surface morphology image, (b) is a vertical amplitude image, (c) is a vertical phase image, and (d) is a vertical phase magnification image.
[0028] Figure 53 and 4. The morphological diagram of the out-of-plane ferroelectric polarization distribution of a single nano-island in the BiFeO3 film with nested skyrmions prepared in Example 1, wherein (a) is the morphology diagram, (b) is the height variation with distance diagram, and (c) is the phase variation with distance diagram.
[0029] Figure 6 Figure 1 is a morphological diagram of the in-plane ferroelectric polarization distribution of nanoislands in the BiFeO3 film with nested skyrmions prepared in Example 1, wherein (a) is a vertical amplitude diagram, (b) is an enlarged diagram of a nanoisland in (a), (c) is a vertical phase diagram, and (d) is an enlarged diagram of a nanoisland in (c); (e) is a horizontal amplitude diagram when the sample is rotated 0° relative to the initial placement position, (f) is an enlarged diagram of a nanoisland in (e), (g) is a horizontal phase diagram when the sample is rotated 0° relative to the initial placement position, and (h) is a nanoisland in (g). ; (i) is the horizontal amplitude diagram when the sample is rotated 45° relative to the initial placement position, (j) is the enlarged image of a nano-island in (i), (k) is the horizontal phase diagram when the sample is rotated 45° relative to the initial placement position, (l) is the enlarged image of a nano-island in (k); (m) is the horizontal amplitude diagram when the sample is rotated 90° relative to the initial placement position, (n) is the enlarged image of a nano-island in (m), (o) is the horizontal phase diagram when the sample is rotated 90° relative to the initial placement position, and (p) is the enlarged image of a nano-island in (o).
[0030] Figure 7 The polarization topological state diagram of the BiFeO3 film with π-nested skyrmions prepared in Example 2, wherein (a) is the amplitude diagram, (b) is the phase diagram, (c) is the result diagram of phase variation with distance, (d) is the three-dimensional vector structure distribution diagram, and (e) is a schematic diagram of the out-of-plane polarization direction distribution.
[0031] Figure 8 The polarization topological state diagram of the BiFeO3 film with π-nested skyrmions prepared in Example 3, wherein (a) is the amplitude diagram, (b) is the phase diagram, (c) is the result diagram of phase variation with distance, (d) is the three-dimensional vector structure distribution diagram, and (e) is a schematic diagram of the out-of-plane polarization direction distribution.
[0032] Fig. 9 The polarization topological state diagram of the BiFeO3 film with 3π nested skyrmions prepared in Example 4, wherein (a) is the amplitude diagram, (b) is the phase diagram, (c) is the result diagram of phase variation with distance, (d) is the three-dimensional vector structure distribution diagram, and (e) is a schematic diagram of the out-of-plane polarization direction distribution. DETAILED DESCRIPTION
[0033] The present invention provides a BiFeO3 thin film with nested skyrmions and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0035] The embodiment of the present invention provides a method for preparing a BiFeO3 thin film having nested skyrmions, which comprises the steps of:
[0036] S1, providing
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0037] S2, with Bi 1.03 FeO3 was used as the target material, and pulsed laser deposition was used to deposit (LaAlO3) oriented in the
[001] direction. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 Deposition is performed on the substrate, and after cooling at a preset cooling rate, a BiFeO3 film with nested skyrmions is obtained; the process parameters used in the pulsed laser deposition method are:
[0038] The temperature is 750~820℃, the oxygen pressure is 70~90mTorr, the laser energy is 300~370mJ, the deposition rate is 8~10Hz, and the deposition time is 5~32min.
[0039] The embodiment of the present invention adopts a pulsed laser deposition method and uses a specific substrate, namely
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71The substrate, specific process parameters (temperature, oxygen pressure, laser energy, deposition time, see above), and the strategy of rapid deposition (deposition rate of 8-10 Hz) are adopted to ensure that the ferroelectric polarization distribution of the prepared BiFeO3 film presents a distribution configuration of polar nested skyrmions (i.e., the preparation of BiFeO3 film with nested skyrmions is achieved). Therefore, the present invention also provides a process for preparing polar nested skyrmion topological states in BiFeO3 film. The method provided by the present invention is simple, controllable, and can realize the industrial production of BiFeO3 film with nested skyrmions. The prepared BiFeO3 film with nested skyrmions has broad application prospects in ferroelectric memory and spintronic devices.
[0040] For example, the temperature is 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C or 820°C, etc. The oxygen pressure is 70mTorr, 72mTorr, 75mTorr, 78mTorr, 80mTorr, 82mTorr, 85mTorr, 88mTorr or 90mTorr, etc. The laser energy is 300mJ, 310mJ, 320mJ, 330mJ, 340mJ, 350mJ, 360mJ or 370mJ, etc. The deposition rate is 8Hz, 8.2Hz, 8.5Hz, 8.8Hz, 9Hz, 9.2Hz, 9.5Hz, 9.8Hz or 10Hz, etc. The deposition time is 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min or 32 min, etc.
[0041] The target material used in the embodiment of the present invention is a polycrystalline sintered ceramic target Bi with a 3% molar excess of Bi. 1.03 The purpose of the excess of Bi is to compensate for the volatilization of Bi during the growth process.
[0042] In some embodiments, the BiFeO3 film with nested skyrmions has a tetragonal phase and a rhombohedral phase. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate exerts compressive strain on the BiFeO3 film, and the tetragonal phase and rhombohedral phase coexist in the BiFeO3 film.
[0043] In some embodiments, the nested skyrmions are classified according to the angular change of the out-of-plane polarization direction, and the type of the nested skyrmions is π-nested skyrmions (i.e., nested skyrmions with an angular change of π in the out-of-plane polarization direction), 2π-nested skyrmions (i.e., nested skyrmions with an angular change of 2π in the out-of-plane polarization direction), or 3π-nested skyrmions (i.e., nested skyrmions with an angular change of 3π in the out-of-plane polarization direction).
[0044] In some embodiments, Figure 1 As shown, the BiFeO3 film 1 with nested skyrmions contains a nano-island structure, and the nano-island structure is composed of a plurality of nano-islands 12. The ferroelectric polarization distribution of the BiFeO3 film containing a plurality of nano-islands presents a distribution configuration of polar nested skyrmions. Specifically, the BiFeO3 film 1 with nested skyrmions is composed of a BiFeO3 film substrate 11 and a plurality of nano-islands 12 located on the BiFeO3 film substrate 11. The ferroelectric polarization distribution of the nanostructure composed of the plurality of nano-islands and the BiFeO3 film substrate in the surrounding area presents a distribution configuration of polar nested skyrmions. Figure 1 As shown, the thickness d of the BiFeO3 film 1 with nested skyrmions is 3~17nm (for example, 3nm, 4nm, 4.5nm, 5nm, 6nm, 6.5nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, 14.5nm, 15nm, 16nm or 17nm, etc.), the thickness d1 of the BiFeO3 film substrate 11 is 0~14nm (for example, 0nm, 1nm, 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 11.5nm, 12nm, 13nm or 14nm, etc.), and the average height d2 of the multiple nano-islands 12 is 2~3nm (for example, 2nm, 2.5nm or 3nm, etc.).
[0045] The BiFeO3 film prepared by the preparation method provided by the embodiment of the present invention has a high-density nano-island structure, which is composed of multiple nano-islands (the nano-islands can be used as storage units). The ferroelectric polarization distribution of the nanostructure composed of multiple nano-islands and the BiFeO3 film matrix in the surrounding area presents a distribution configuration of polar nested skyrmions. Therefore, the BiFeO3 film can be used in ferroelectric memory (especially non-volatile high-density ferroelectric memory).
[0046] Taking the plane direction of the BiFeO3 film with nested skyrmions as the lateral direction and the thickness direction of the BiFeO3 film with nested skyrmions as the longitudinal direction, the average particle size of the multiple nano-islands in the lateral direction is 100~400nm, and the average particle size of the multiple nano-islands in the longitudinal direction is 2~3nm (that is, the average height d2 of the multiple nano-islands is 2~3nm).
[0047] In an embodiment of the present invention, at a temperature of 800°C, an oxygen pressure of 90mTorr, a laser energy of 370mJ, and a deposition rate of 10Hz, the thickness of the BiFeO3 film with nested skyrmions can be controlled by adjusting the deposition time (or, the thickness of the BiFeO3 film matrix can be controlled), and then the average particle size of multiple nano-islands in the lateral direction can be controlled, and finally the ferroelectric polarization distribution configuration of the BiFeO3 film can be controlled.
[0048] Specifically, in some embodiments, when the deposition time is 6 to 9 minutes, the thickness of the obtained BiFeO3 film with nested skyrmions is 3 to 4.5 nm, the average particle size of the multiple nano-islands in the lateral direction is 100 to 200 nm, and the type of the nested skyrmions is π-nested skyrmions.
[0049] In some embodiments, when the deposition time is 10-15 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 6-7 nm, the average particle size of the plurality of nano-islands in the lateral direction is 350 nm, and the nested skyrmions are 2π nested skyrmions.
[0050] In some embodiments, when the deposition time is 25-32 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 14-17 nm, the average particle size of the multiple nano-islands in the lateral direction is 400 nm, and the type of the nested skyrmions is 3π nested skyrmions.
[0051] In some embodiments, the preset cooling rate is 5-10°C / min, for example, the preset cooling rate is 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, etc. In this embodiment, after the BiFeO3 film with nested skyrmions is grown in the pulsed laser deposition system, the BiFeO3 film with nested skyrmions is taken out after the system is cooled down for annealing, and the cooling rate, i.e., the annealing rate, drops to room temperature.
[0052] An embodiment of the present invention further provides a BiFeO3 film with nested skyrmions, wherein the film is prepared by the preparation method of the present invention as described above.
[0053] The embodiment of the present invention further provides an application of the BiFeO3 thin film with nested skyrmions as described above in a ferroelectric memory. In some specific implementations, the ferroelectric memory is a non-volatile ferroelectric memory.
[0054] Since the BiFeO3 film provided in the embodiment of the present invention has a high-density nano-island structure (composed of multiple nano-islands), and the ferroelectric polarization distribution of the nanostructure composed of multiple nano-islands and the BiFeO3 film matrix in the surrounding area presents a distribution configuration of polar nested skyrmions, the BiFeO3 film can be used in ferroelectric memory, especially in non-volatile high-density ferroelectric memory.
[0055] The present invention will be further described below by means of specific examples.
[0056] Unless otherwise specified in the following examples, the raw materials and equipment used are all commercially available products.
[0057] The laser of the pulsed laser deposition system used in the following embodiments is a COMPExPro 102 KrF excimer laser (wavelength λ=248nm) produced by Coherent Corporation of the United States, and the vacuum chamber is a Pioneer 180-2 ultra-high vacuum chamber produced by Neocera Corporation of the United States.
[0058] Example 1
[0059] This embodiment provides a method for preparing a BiFeO3 thin film having nested skyrmions, which comprises the following steps:
[0060] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0061] The
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at that temperature for 1 h;
[0062] Then, with Bi 1.03 FeO3 was used as the target material, and the temperature was 800°C, the oxygen pressure was 90mTorr, the laser energy was 370mJ, and the deposition rate was 10Hz. 0.29 (SrTa 1 / 2 Al1 / 2 O3) 0.71 The substrate was subjected to pulsed laser deposition for 13 min, and then cooled to room temperature at a cooling rate of 10 °C / min to obtain a BiFeO3 film with nested skyrmions, wherein Figure 1 As shown, it was measured that the thickness d of the BiFeO3 film with nested skyrmions was 6.5 nm, the thickness d1 of the BiFeO3 film matrix was 3.5 nm, and the average height d2 of the multiple nano-islands was 3 nm.
[0063] test:
[0064] (1) X-ray diffraction test was performed on the BiFeO3 film with nested skyrmions prepared in Example 1. The results are as follows: Figure 2 As shown, BFO represents BiFeO3 and LSAT represents (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.7 It can be seen that the 2θ of 43.69° and 45.52° correspond to the (002) crystal plane of the tetragonal (T-like phase) structure and rhombohedral (R phase) structure of BiFeO3, respectively, that is, the BiFeO3 film has both tetragonal and rhombohedral phase structures. This is because (LaAlO3) 0.29 (SrTa 1 / 2Al 1 / 2 O3) 0.71 This is caused by the compressive strain exerted by the substrate on BiFeO3.
[0065] (2) The BiFeO3 film with nested skyrmions prepared in Example 1 was subjected to grazing incidence wide angle X-ray scattering (GIWAXS) test. The results are as follows: Figure 3 As shown, q z represents the out-of-plane vector, q x Represents an in-plane vector parallel to the incident plane, rlu is a relative length unit, LSAT represents (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.7 , R-BFO represents rhombohedral BiFeO3, and T-like BFO represents quasi-tetragonal BiFeO3. It can be seen that the BiFeO3 film has a good orientation, and both quasi-tetragonal and rhombohedral phase structures exist.
[0066] (3) The BiFeO3 film with nested skyrmions prepared in Example 1 was tested by piezoelectric force microscopy (PFM). The results are as follows: Figure 4As shown, the BiFeO3 film has a high-density nano-island structure (composed of multiple nano-islands, and one particle in the figure represents a nano-island). In the plane direction of the BiFeO3 film, the average particle size of the multiple nano-islands is 350nm.
[0067] (4) The out-of-plane ferroelectric polarization distribution morphology of a single nano-island in the BiFeO3 film with nested skyrmions prepared in Example 1 is as follows: Figure 5 As shown, it can be seen that the inner core and outer ring of the nano-island have opposite out-of-plane polarizations, and the outer ring of the nano-island and the surrounding BiFeO3 film matrix also have opposite out-of-plane polarizations (similar to a donut shape).
[0068] (5) The distribution morphology of the in-plane ferroelectric polarization of the nano-islands in the BiFeO3 film with nested skyrmions prepared in Example 1 is as follows: Figure 6 As shown, through the in-plane ferroelectric polarization distribution and the amplitude and phase results in the out-of-plane direction, after reconstruction, it is determined that the in-plane polarization distribution of the nano-island is an outward divergent or inward convergent configuration, and the polar topological state in the nano-island is a 2π nested skyrmion.
[0069] Example 2
[0070] This embodiment provides a method for preparing a BiFeO3 thin film having nested skyrmions, which comprises the following steps:
[0071] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0072] The
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at that temperature for 1 h;
[0073] Then, with Bi 1.03 FeO3 was used as the target material, and the temperature was 800°C, the oxygen pressure was 90mTorr, the laser energy was 370mJ, and the deposition rate was 10Hz. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 Pulsed laser deposition was performed on the substrate for 6 min, and then the temperature was cooled to room temperature at a cooling rate of 10 °C / min to obtain a BiFeO3 film with nested skyrmions. Figure 1As shown, it has been measured that in this embodiment, the thickness d of the BiFeO3 film with nested skyrmions is 3 nm, the thickness d1 of the BiFeO3 film matrix is 0 nm, and the average height d2 of the plurality of nano-islands is 3 nm.
[0074] The polarization topological state results of the BiFeO3 film with nested skyrmions in Example 2 are as follows: Figure 7 The results show that in the plane direction of the BiFeO3 film, the average particle size of multiple nano-islands is 100nm, and the polar topological state is π-nested skyrmions.
[0075] Example 3
[0076] This embodiment provides a method for preparing a BiFeO3 thin film having nested skyrmions, which comprises the following steps:
[0077] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0078] The
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at that temperature for 1 h;
[0079] Then, with Bi 1.03 FeO3 was used as the target material, and the temperature was 800°C, the oxygen pressure was 90mTorr, the laser energy was 370mJ, and the deposition rate was 10Hz. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 Pulsed laser deposition was performed on the substrate for 9 min, and then the temperature was cooled to room temperature at a cooling rate of 10 °C / min to obtain a BiFeO3 film with nested skyrmions. Figure 1 As shown, it was measured that the thickness d of the BiFeO3 film with nested skyrmions was 4.5 nm, the thickness d1 of the BiFeO3 film matrix was 2.5 nm, and the average height d2 of the multiple nano-islands was 2 nm.
[0080] The polarization topological state results of the BiFeO3 film with nested skyrmions in Example 3 are as follows: Figure 8The results show that in the plane direction of the BiFeO3 film, the average particle size of multiple nano-islands is 200nm, and the polar topological state is π-nested skyrmions.
[0081] Example 4
[0082] This embodiment provides a method for preparing a BiFeO3 thin film having nested skyrmions, which comprises the following steps:
[0083] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0084] The
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at that temperature for 1 h;
[0085] Then, with Bi 1.03 FeO3 was used as the target material, and the temperature was 800°C, the oxygen pressure was 90mTorr, the laser energy was 370mJ, and the deposition rate was 10Hz. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was subjected to pulsed laser deposition for 29 min, and then cooled to room temperature at a cooling rate of 10 °C / min to obtain a BiFeO3 film with nested skyrmions. Figure 1 As shown, it was measured that the thickness d of the BiFeO3 film with nested skyrmions was 14.5 nm, the thickness d1 of the BiFeO3 film matrix was 11.5 nm, and the average height d2 of the multiple nano-islands was 3 nm.
[0086] The polarization topological state results of the BiFeO3 film with nested skyrmions in Example 4 are as follows: Fig. 9 The results show that in the plane direction of the BiFeO3 film, the average particle size of multiple nano-islands is 400nm, and the polar topological state is 3π nested skyrmions.
[0087] Comparative Example 1
[0088] This comparative example provides a method for preparing a BiFeO3 thin film, which comprises the following steps:
[0089] Providing a
[001] -oriented SrTiO3 substrate;
[0090] The
[001] -oriented SrTiO3 substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at this temperature for 1h;
[0091] Then, with Bi 1.03 FeO3 was used as the target material. Pulsed laser deposition was carried out on the
[001] oriented SrTiO3 substrate for 13 minutes at a temperature of 800°C, an oxygen pressure of 90mTorr, a laser energy of 370mJ, and a deposition rate of 6Hz. After cooling to room temperature at a cooling rate of 10°C / min, a BiFeO3 film with nested skyrmions could not be obtained.
[0092] Comparative Example 2
[0093] This comparative example provides a method for preparing a BiFeO3 thin film, which comprises the following steps:
[0094] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate;
[0095] The
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at that temperature for 1 h;
[0096] Then, with Bi 1.03 FeO3 was used as the target material, and the temperature was 800°C, the oxygen pressure was 90mTorr, the laser energy was 370mJ, and the deposition rate was 3Hz. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 After pulsed laser deposition on the substrate for 13 min and then cooling to room temperature at a cooling rate of 10 °C / min, no BiFeO3 film with nested skyrmions could be obtained.
[0097] Comparative Example 3
[0098] This comparative example provides a method for preparing a BiFeO3 thin film, which comprises the following steps:
[0099] Provides
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2Al 1 / 2 O3) 0.71 substrate;
[0100] The
[001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The substrate was placed in the chamber of a pulsed laser deposition system, heated to 800°C at a heating rate of 15°C / min and kept at that temperature for 1 h;
[0101] Then, with Bi 1.03 FeO3 was used as the target material, and the temperature was 800°C, the oxygen pressure was 90mTorr, the laser energy was 370mJ, and the deposition rate was 5Hz. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 After pulsed laser deposition on the substrate for 13 min and then cooling to room temperature at a cooling rate of 10 °C / min, no BiFeO3 film with nested skyrmions could be obtained.
[0102] In summary, the present invention provides a BiFeO3 film with nested skyrmions and a preparation method and application thereof. The present invention adopts a pulsed laser deposition method to prepare a (LaAlO3) film with a specific
[001] orientation. 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 The method provided by the invention is simple, controllable and can realize industrial production. The prepared BiFeO3 film with nested skyrmions has broad application prospects in ferroelectric memory and spin electronic devices.
[0103] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a BiFeO3 thin film having nested skyrmions, characterized in that: Includes steps: Provides [001] oriented (LaAlO3) 0.29 (SrTa 1 / 2 Al 1 / 2 O3) 0.71 substrate; Bi 1.03 FeO3 was used as the target material, and pulsed laser deposition was used to deposit (LaAlO3) oriented in the [001] direction. 0.29 (SrTa 1 / 2 Al 1 / 2O3) 0.71 Deposition is performed on a substrate, and after cooling at a preset cooling rate, a BiFeO3 film with nested skyrmions is obtained; The process parameters used in the pulsed laser deposition method are: The temperature is 750~820℃, the oxygen pressure is 70~90mTorr, the laser energy is 300~370mJ, the deposition rate is 8~10Hz, and the deposition time is 5~32min; The BiFeO3 film with nested skyrmions contains both tetragonal-like BiFeO3 and rhombohedral BiFeO3; Classification is performed based on the angular change of the out-of-plane polarization direction of the nested skyrmions, wherein the nested skyrmions are of the type of π-nested skyrmions, 2π-nested skyrmions, or 3π-nested skyrmions; The BiFeO3 film with nested skyrmions contains a nano-island structure, which is composed of a plurality of nano-islands. The ferroelectric polarization distribution of the BiFeO3 film containing a plurality of nano-islands presents a distribution configuration of polar nested skyrmions. Taking the plane direction of the BiFeO3 film with nested skyrmions as the lateral direction and the thickness direction of the BiFeO3 film with nested skyrmions as the longitudinal direction, the average particle size of the multiple nano-islands in the lateral direction is 100~400nm, and the average particle size of the multiple nano-islands in the longitudinal direction is 2~3nm.
2. The method for preparing a BiFeO3 thin film having nested skyrmions according to claim 1, characterized in that: The thickness of the BiFeO3 film with nested skyrmions is 3-17 nm.
3. The method for preparing a BiFeO3 thin film having nested skyrmions according to claim 1, characterized in that: When the deposition time is 6-9 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 3-4.5 nm, the average particle size of the multiple nano-islands in the lateral direction is 100-200 nm, and the type of the nested skyrmions is π-nested skyrmions.
4. The method for preparing a BiFeO3 thin film having nested skyrmions according to claim 1, characterized in that: When the deposition time is 10-15 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 6-7 nm, the average particle size of the multiple nano-islands in the lateral direction is 350 nm, and the type of the nested skyrmions is 2π nested skyrmions.
5. The method for preparing a BiFeO3 thin film having nested skyrmions according to claim 1, characterized in that: When the deposition time is 25-32 min, the thickness of the obtained BiFeO3 film with nested skyrmions is 14-17 nm, the average particle size of the multiple nano-islands in the lateral direction is 400 nm, and the type of the nested skyrmions is 3π nested skyrmions.
6. The method for preparing a BiFeO3 thin film having nested skyrmions according to claim 1, characterized in that: The preset cooling rate is 5-10°C / min.
7. A BiFeO3 film with nested skyrmions, characterized in that: The film is prepared by the method for preparing a BiFeO3 film with nested skyrmions as described in any one of claims 1 to 6.
8. Use of the BiFeO3 film with nested skyrmions as claimed in claim 7 in a ferroelectric memory.